ANTIBACTERIAL ACTIVITY AND TLC-BIOAUTOGRAPHY ANALYSIS OF THE ACTIVE FRACTIONS OF Muntingia calabura L. LEAVES AGAINST Staphylococcus aureus - Rizky H. Mawardi; Nanik Sulistyani; Nurkhasanah Nurkhasanah; Ricke Desyratnaputri (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2020)
This study aims to determine the antibacterial activity and TLC-bioautography profile of the active fractions of Muntingia calabura L. leaves against Staphylococcus aureus. Muntingia calabura L. leaves were macerated with ethanol 96% then fractionated with n-hexane, ethyl acetate, and methanol solvent, respectively. The antibacterial activity was tested by the Kirby-Bauer method to determine the most active fraction and the lowest concentration that inhibited the growth of Staphylococcus aureus. TLC-bioautography was tested using chloroform: ethyl acetate (2:8) as the mobile phase and silica gel F254 as the stationary phase. Antibacterial activity test of n-hexane and ethyl acetate fractions at a concentration of 10% w/v showed activities with inhibition zone diameter of 0.330.288 and 9.665.77 mm, respectively. At the same time, the methanol fraction showed no activity. The lowest concentration of ethyl acetate fraction which still showed the inhibition zone was 0.312% w/v. The TLC-bioautography profile showed active spots with an Rf value of 0.82 and had an inhibitory zone diameter of 4.0130.864 mm. It can be concluded that the ethyl acetate fraction was the most active fraction that inhibited the growth of Staphylococcus aureus and had one active spot on the bioautography test.